2022
DOI: 10.33086/jhcs.v2i2.2817
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Role of the Family in Preventing and Handling Stunting in the Covid 19 Pandemic

Abstract: One of the important foundations in toddlerhood is good and healthy nutritional status. However, there were still many problems with nutritional status at that time, one of which was stunting in toddlers. This condition occurs due to parents' lack of awareness and knowledge regarding the pattern of fulfilling nutrition, especially in toddlers. The lack of awareness and knowledge of mothers about bad parenting practices, the variety of ingredients and the variety of types of food provided to fulfill nutrition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This Health Education activity has a big influence on changing a person's level of knowledge. This is in line with research results which found that the majority of cadres already knew cadre duties related to monitoring growth and development (Ludyanti et al, 2022). Knowledge is a human reaction to stimulation by the natural environment through contact with objects with the senses which is based on knowledge which is more lasting than behavior which is not based on knowledge.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This Health Education activity has a big influence on changing a person's level of knowledge. This is in line with research results which found that the majority of cadres already knew cadre duties related to monitoring growth and development (Ludyanti et al, 2022). Knowledge is a human reaction to stimulation by the natural environment through contact with objects with the senses which is based on knowledge which is more lasting than behavior which is not based on knowledge.…”
Section: Discussionsupporting
confidence: 87%
“…Based on the results of interviews with cadres, it was stated that not all posyandu cadres knew the technicalities of monitoring developmental disorders in children. due to lack of information and the presence of new cadres who have not been trained (Ludyanti et al, 2022) This is proven to have an influence on the results of the knowledge assessment before and after being given Health Education (Cumayunaro et al, 2020;Lisnawati et al, 2022;Nurul Abidah & Novianti, 2020) The research results showed that more than half of the respondents had poor knowledge, 26 (52%), whereas after being given Health Education, 38 people (76%) experienced an increase in the good category. If we look at the Wilcoxon test, we get a p-value of 0.000 < 0.05, then Ho is rejected and Ha is accepted, meaning that there is a difference in the level of knowledge of respondents before and after being given health education.…”
Section: Discussionmentioning
confidence: 99%